Factors Related to Anxiety Levels of the Elderly with Chronic Diseases in Sijunjung Regency 2019: Faktor-Faktor yang Berhubungan dengan Tingkat Kecemasan Lansia dengan Penyakit Kronis di Kabupaten Sijunjung Tahun 2019 - Herlin Silvana; Defriman Djafri; Renidayati (NERS Jurnal Keperawatan, 2019)
of anxiety increases. As the number of elderly increases, it is very important to maintain the health of the elderly. Otherwise, it will result in the decreased physical condition, limited mobility, decreased independence, loss of self-confidence and decreased social activity. Knowing and controlling the causative factors of anxiety can be a solution to overcome anxiety in the elderly. This study aimed to measure the factors associated with the anxiety level of the elderly with chronic deseases in Sijunjung Regency. The design of this study was cross sectional approach and logistic multivariable regressions method. The samples were chosen by a cluster sampling technique with a total of 207 elderly with chronic diseases. The results showed that income, social support, social activities, and history of trauma had a significant relationship with the anxiety level of the elderly with chronic deseases and social support is the most dominant factor that related to. Thus, it was suggested to increase the nursing interventions with an approach family therapy to increase social support and it was focused on improving regular health screening so that the occurence of chronic deseases and anxiety in the elderly could be identified earlier.